Footnotes to Disciples History - Haggard, Rice (Disciples of Christ Historical Society, 2020)
From the mid 1950s through the 1990s, DCHS printed short publications to remind its readers about the importance of the past. The series included reprints as well as new historical studies. Footnotes to Disciples History collects this wide-ranging series into one volume. Rice Haggard's An Address to the Different Religious Societies, on the sacred import of the Christian Name (1804); ⁃ John M. Imbler's Beyond Buffalo: Alexander Campbell on Education for Ministry (1992); ⁃ Report of the Proceedings of a General Meeting of Messengers from Thirteen Congregations (J.T. McVay and Alexander Campbell, 1834); William A. Gerrards's Christian Unity, Our Heritage (1986); Alexander Campbell's Lunenburg Letter (1837); ⁃ Eva Jean Wrather's Alexander Campbell and His Relevance for Today (1959); Perry Gresham's The Broncho That Would Not Be Broken (1986)